Exploration of acute and chronic anti-inflammatory potential of Quercus leucotrichophora A. Camus extracts in Wistar rats: A mechanistic insight - Saleem, Ammara; Hameed, Izza; Akhtar, Muhammad Furqan; Ashraf, Ghulam Md; Alghamdi, Badrah S.; Rahman, Md. Habibur; Almashjary, Majed N. (Frontiers in Pharmacology, 2023)
Introduction: This research was conducted to validate the folkloric use of Quercus leucotrichophora (QL) leaf extracts against inflammation and arthritis and to determine the chemical composition using HPLC. Method: The aqueous and methanolic extracts of QL were evaluated by in vitro anti-oxidant, anti-inflammatory (inhibition of protein denaturation and membrane stabilization) assays, and in vivo anti-inflammatory (carrageenan and xylene-induced edema) and anti-arthritic models. For anti-arthritic potential, 0.1 mL Complete Freund’s Adjuvant (CFA) was inoculated into the left hind paw of a Wistar rat on day 1, and oral dosing with QL methanolic extract (QLME) at 150, 300, and 600 mg/kg was begun at day 8 till the 28th day in all groups, except disease control that was given distilled water, while methotrexate was given as standard treatment. Results and discussion: There was a noteworthy (p < 0.05–0.0001) restoration in body weight, paw edema, arthritic index, altered blood parameters, and oxidative stress biomarkers in treated rats as compared to the diseased group. Moreover, QLME treatment significantly (p < 0.0001) downregulated TNF-α, IL-6, IL-1β, COX-2, and NF-κB, while significantly (p < 0.0001) upregulating IL-10, I-κB, and IL-4 in contrast to the diseased group. The QLME exhibited no mortality in the acute toxicity study. It was concluded that QLME possessed substantial anti-oxidant, anti-inflammatory, and anti-arthritic potential at all dosage levels prominently at 600 mg/kg might be due to the presence of quercetin, gallic, sinapic, and ferulic acids.